Is HRQOL in dialysis associated with patient survival or graft function after kidney transplantation?. Issue 1 (December 2016) - von der Lippe, Nanna; Waldum-Grevbo, Bård; Varberg Reisæter, Anna; Os, Ingrid
Abstract Background Health related quality of life (HRQOL) is patient-reported, and an important treatment outcome for patients undergoing renal replacement therapy. Whether HRQOL in dialysis can affect mortality or graft survival after renal transplantation (RTX) is not determined. The aims of the present study were to investigate whether pretransplant HRQOL is associated with post-RTX patient survival or graft function, and to assess whether improvement in HRQOL from dialysis to RTX is associated with patient survival. Methods In a longitudinal prospective study, HRQOL was measured in 142 prevalent dialysis patients (67 % males, mean age 51 ± 15.5 years) who subsequent underwent renal transplantation. HRQOL could be repeated in 110 transplant patients 41 (IQR 34–51) months after RTX using the self-administered Kidney Disease and Quality of Life Short Form (KDQOL-SF) measure. Kaplan-Meier plots were utilized for survival analyses, and linear regression models were used to address HRQOL and effect on graft function. Results Follow-up time was 102 (IQR 97–108) months after RTX. Survival after RTX was higher in patients who perceived good physical function (PF) in dialysis compared to patients with poorer PF (p  = 0.019). Low scores in the domain mental health measured in dialysis was associated with accelerated decline in graft function (p  = 0.048). Improvements in the kidney-specific domains "symptoms" and "effect of kidney disease" in the trajectory from dialysis to RTX were associated with a survival benefit (p  = 0.007 andp  = 0.02, respectively). Conclusion HRQOL measured in dialysis patients was associated with survival and graft function after RTX. These findings may be useful in clinical pretransplant evaluations. Improvements in some of the kidney-specific HRQOL domains from dialysis to RTX were associated with lower mortality. Prospective and interventional studies are warranted.